SDG 5 at UFMS: Building an Equal Academic Environment for Women - Luciana Contrera; Leonardo Chaves de Carvalho; Joao Vitor Costa; Helder Samuel dos Santos Lima; Anacarla Previato Nunes; Ingrid Queiroz Oliveira de Souza; Vivina Dias Sol Queiroz; Camila Celeste Brandao Ferreira Itavo; Albert Schiaveto de Souza (Universitas Diponegoro, 2025)
This article examines the trajectory and advances of the Sou Mulher UFMS (“I am a Woman UFMS”) program, implemented by the Federal University of Mato Grosso do Sul (UFMS), in the context of SDG 5 – Gender Equality of the UN 2030 Agenda. Adopting a qualitative, documentary approach, the study applies thematic analysis to institutional data and strategic documents — including the Institutional Development Plan (PDI), Annual Management Reports, Institutional Committees Meetings, and Public Records from 2021 to 2024. The results reveal the program’s evolution from isolated actions to a structured institutional policy, supported by intersectoral governance, evidence-based planning, and the strengthening of institutional bodies such as the Pro-rectorate for Citizenship and Sustainability (Procids) and the Committee for People Management, Inclusion, and Affirmative Actions (CGPIA). Key achievements include greater female representation and leadership, enhanced support for maternity and paternity in academia, and reinforced mechanisms for preventing and addressing gender-based violence. The updated program for 2025–2028 sets measurable, sustainable goals to promote equity in admission, retention, and academic success for women, with attention to diversity and intersectionality. The UFMS experience offers a replicable model for other higher education institutions in Brazil and Latin America, demonstrating the transformative potential of institutionalized gender policies driven by data, participation, and strategic governance.